Assessment of medical courses in Brazil using student-completed questionnaires. Is it reliable? - Peluso, Marco Aurélio Monteiro; Tavares, Hermano; D'Elia, Gilberto (Revista do Hospital das Clínicas, 2000)
INTRODUCTION: Debates about the quality of medical education have become more evident in the recent past, and as a result several different assessment methods have been refined for that purpose. The use of questionnaires filled out by medical students to assess the quality of lectures is one of the most common methods employed in our milieu. However, the reliability of this investigation method has not yet been systematically tested. The authors present the reliability of a specific form applied to the fourth grade medical students during the clinical psychiatry course. METHOD: Eighty-one fourth grade medical students were instructed to complete a form immediately after each clinical psychiatry lecture. Thirty-four students (42%) failed to turn in the forms after the final lecture. These students were given an identical form to assess the lectures in a retrospective fashion. The grades given by both groups of students for each performed lecture and the number of students who have graded an unperformed lecture were compared. Statistical significance for both groups was determined by means of the chi-square test (p< 0.05). RESULTS: Eighteen out of the 34 students who filled out the forms retrospectively (53%) rated the unperformed lecture, whereas only 5 out of the 47 students who filled out the forms during the course (11%) did so. This is statistically significant (p< 0.05). There was no statistical difference for the grades given to the lectures that were actually performed. DISCUSSION: The authors concluded the low reliability rate of the retrospective evaluation warrant a continuous assessment method during the course.